Detection of High-Risk Human Papillomavirus in Cervix Sample in an 11.3-year Follow-Up after Vaccination against HPV 16/18 - Teixeira, Cirbia Silva Campos; Teixeira, Julio Cesar; Oliveira, Eliane Regina Zambelli Mesquita; Machado, Helymar Costa; Zeferino, Luiz Carlos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose the aim of this study was to evaluate the pattern of human papillomavirus (HPV) detection in an 11.3-year post-vaccination period in a cohort of adolescent and young women vaccinated or not against HPV 16/18.Methods a subset of 91 women from a single center participating in a randomized clinical trial (2001–2010, NCT00689741/00120848/00518336) with HPV 16/18 AS04-adjuvanted vaccine was evaluated. All women received three doses of the HPV vaccine (n = 48) or a placebo (n = 43), and cervical samples were collected at 6-month intervals. Only in this center, one additional evaluation was performed in 2012. Up to 1,492 cervical samples were tested for HPV-DNA and genotyped with polymerase chain reaction (PCR). The vaccine group characteristics were compared by Chi-square or Fisher exact or Mann-Whitney test. The high-risk (HR)-HPV 6-month-persistent infection rate was calculated. The cumulative infection by HPV group was evaluated by the Kaplan-Meier method and the log-rank test.Results the cumulative infection with any type of HPV in an 11.3-year period was 67% in the HPV vaccine group and 72% in the placebo group (p = 0.408). The longitudinal analysis showed an increase of 4% per year at risk for detection of HR-HPV (non-HPV 16/18) over time (p = 0.015), unrelated to vaccination. The cumulative infection with HPV 16/18 was 4% for the HPV vaccine group and 29% for the placebo group (p = 0.003). There were 43 episodes of HR-HPV 6-month persistent infection, unrelated to vaccination.Conclusions this study showed the maintenance of viral detection rate accumulating HR-HPV (non-HPV-16–18) positive tests during a long period post-vaccination, regardless of prior vaccination. This signalizes that the high number of HPV-positive tests may be maintained after vaccination.
Keywords: human papillomavirus; cervix uteri; papillomavirus vaccines; human papillomavirus vaccine 16 and 18 L1 VLP; HPV DNA tests; polymerase chain reaction